Thinkertoys : a handbook of creative-thinking techniques. - Michalko, Michael, 1940- (Berkeley : Ten Speed, 2006)
This is an updated and expanded edition of the best-selling Thinkertoys, which is considered by many to be the classic book of creative thinking techniques. The original ground-breaking first edition was widely acclaimed by readers and reviewers. The Wall Street Journal reported 'this book will change the way you think." Women In Business lauded it as "one of the most important business titles of the decade," Success magazine described it as a "fun-to-read book which helps you to create and act on ideas," USA said "believe it or not, this wonderful book will have you challenging the seemingly impossible every day," Executive Book Summaries praised it by saying, "What we need is a compendium of ways to solve problems. And that's exactly what you get in Thinkertoys" Entrepreneur acclaimed it as "required reading for anyone in business," the Futurist said "Thinkertoys" shows you how to do what you think can't be done," and the AMA called it "the most significant book on creativity published in the last twenty years." This new edition contains updated examples, three new Thinkertoys and an entirely new group brainstorming section with five new chapters. Michael is also the author of Thinkpak (A Brainstorming Card Set), which is a novel creative-thinking tool that is designed to facilitate brainstorming sessions and Cracking Creativity (The Secrets of Creative Geniuses) which describes the common thinking strategies creative geniuses have used in the sciences, art, and industry throughout history and shows how we can apply them to become more creative in our business and personal lives.
Keywords: Creatief denken; Creative thinking